2017
DOI: 10.1177/2045893217709025
|View full text |Cite
|
Sign up to set email alerts
|

Functional impact of exercise pulmonary hypertension in patients with borderline resting pulmonary arterial pressure

Abstract: Borderline resting mean pulmonary arterial pressure (mPAP) is associated with adverse outcomes and affects the exercise pulmonary vascular response. However, the pathophysiological mechanisms underlying exertional intolerance in borderline mPAP remain incompletely characterized. In the current study, we sought to evaluate the prevalence and functional impact of exercise pulmonary hypertension (ePH) across a spectrum of resting mPAP’s in consecutive patients with contemporary resting right heart catheterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 43 publications
5
39
0
Order By: Relevance
“…Oliveira et al found that exercise‐induced PH was most frequently seen in patients with a mean PAP of 21–24 mm Hg, who have a reduction in exercise capacity similar to that in patients with resting PH . In the present study, 22 (30.6%) of 72 patients with a mean PAP of <21 mm Hg at rest fulfilled the criteria for exercise‐induced PH versus 11 (78.6%) of 14 patients with a mean PAP of 21–24 mm Hg, consistent with the observations of Oliveira et al . However, in our study, regression and correlation analysis revealed a significant correlation of PAC at rest with 6‐minute walking distance (R = 0.448, P < 0.001) (Figure ) and ΔCO (R = 0.227, P = 0.018) and a trend toward correlation of PAC at rest with ΔCI (R = 0.178, P = 0.064).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Oliveira et al found that exercise‐induced PH was most frequently seen in patients with a mean PAP of 21–24 mm Hg, who have a reduction in exercise capacity similar to that in patients with resting PH . In the present study, 22 (30.6%) of 72 patients with a mean PAP of <21 mm Hg at rest fulfilled the criteria for exercise‐induced PH versus 11 (78.6%) of 14 patients with a mean PAP of 21–24 mm Hg, consistent with the observations of Oliveira et al . However, in our study, regression and correlation analysis revealed a significant correlation of PAC at rest with 6‐minute walking distance (R = 0.448, P < 0.001) (Figure ) and ΔCO (R = 0.227, P = 0.018) and a trend toward correlation of PAC at rest with ΔCI (R = 0.178, P = 0.064).…”
Section: Discussionsupporting
confidence: 92%
“…The combination of a mean PAP of 21–24 mm Hg and exercise‐induced PH in that population was associated with worse functional capacity , increased progression to resting PH , and worse survival . Oliveira et al found that exercise‐induced PH was most frequently seen in patients with a mean PAP of 21–24 mm Hg, who have a reduction in exercise capacity similar to that in patients with resting PH . In the present study, 22 (30.6%) of 72 patients with a mean PAP of <21 mm Hg at rest fulfilled the criteria for exercise‐induced PH versus 11 (78.6%) of 14 patients with a mean PAP of 21–24 mm Hg, consistent with the observations of Oliveira et al .…”
Section: Discussionsupporting
confidence: 48%
“…; Oliveira et al . ). Clinically, group II PH comprises a variety of different aetiologies, including left HF, valvular disease, inflow‐/outflow‐tract obstructions, and congenital or acquired pulmonary vein stenosis.…”
Section: Discussionmentioning
confidence: 97%
“…The additional chronic instrumentation, and subsequent exercise testing unmasked a mild chronotropic incompetence that has also been shown in PH (Oliveira et al . ), and has been ascribed to impaired autonomic control (Bristow et al . ; Wensel et al .…”
Section: Discussionmentioning
confidence: 99%
“…5 Twenty five percent to 86% of patients with resting mPAP 21-24 mmHg have ePH. 6,7 ePH itself is associated with overt symptoms, reduced exercise capacity, and poorer clinical outcomes. 3,[8][9][10][11][12][13] Exercise PH may represent an early and clinically relevant stage of pulmonary arterial hypertension (PAH).…”
Section: Introductionmentioning
confidence: 99%